Evaluasi Proses Bisnis menggunakan menggunakan Quality Evaluation Framework (QEF) pada CV. Jiwo Elektro - Adithia Sandi Josua; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Technology is a world that is always evolving over time. Technological developments have now reached the stage of integration with business. In its implementation, of course the business will also participate in making changes and improvements in order to achieve the organization's vision and mission. CV. Jiwo Elektro is an organization engaged in manufacturing. In carrying out its business processes, the organization has targets that must be met in order to achieve its vision and mission. The existing business processes in the organization have also been integrated with the information technology used. To achieve these targets, it is necessary to evaluate the performance of the organization, especially during the current pandemic which greatly affects the performance of existing business processes. By evaluating the business processes running in the organization, it is hoped that the evaluation results can improve the efficiency and effectiveness of business processes so that organizational goals can be fully achieved. In this study, researchers evaluate existing business processes using the Quality Evaluation Factor (QEF) method. QEF is an evaluation method that focuses on the suitability of the targets set by the organization (quality factor) with the reality that occurs in the field. For this reason, before conducting an evaluation, researchers will first model the existing business processes in the organization. This business process modeling is carried out using the Bizagi application. To model the business process, the researcher collected data by using the interview method with the relevant stakeholders. After conducting interviews and modeling business processes, the researcher will conduct further interviews with decision makers regarding the quality factors or organizational targets that have been set. Then the researcher evaluates the data obtained by comparing the target with field data. The results of the evaluation will then become the results of this research and it is hoped that these results can be used by organizations for decision making in the future.